The Poetics Of Imagery In Contemporary Uzbek Poetry - Prof. Umida Rasulova (European International Journal of Pedagogics, 2025)
With independence, attitudes toward customes, national values, culture, and in particular, the Literature have undergone fundamental changes. The new era requires a renewed ideological and aesthetic approach not only to the history of our literature but also to the modern literary and artistic process. The psychological scale and artistic potential of contemporary Uzbek poetry are growing day by day. In this sense, lyric poetry occupies a special place in modern Uzbek literature. It not only reflects the feelings and emotions experienced in the hearts of our contemporaries but also helps to strengthen gratitude for independence and faith in a bright future among members of society. Revealing the nature of today’s poetry and its underlying philosophical ideas, as well as determining its leading ideological and artistic principles, allows us to predict the future development of Uzbek poetry.